2005
DOI: 10.2174/092986705774933416
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Inhibition and Cancer: Might Platinum Based Drugs have a Future as Anti-telomerase Pharmacological Approach?

Abstract: Telomerase is a ribonucleoprotein polymerase that maintains the length of telomeric DNA by adding hexameric units (TTAGGG) to the ends of the chromosomes. This mechanism prevents replicative senescence, thus conferring unlimited proliferative potential to cells. Telomerase reactivation has been detected in most human tumour tissue, indicating that the enzyme may be useful as a specific tumour marker. The inhibition of telomerase causes a progressive and critical reduction of telomeres, leading to a potent sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 255 publications
(298 reference statements)
0
10
0
Order By: Relevance
“…13) Most normal human cells have no detectable telomerase activity, but it is observed in most cancer cells 14,15) The inhibition of telomerase causes a progressive and critical reduction of telomeres, leading to a potent signal for the blockage of cell proliferation and the induction of apoptosis. 16) Targeting the inhibition of telomerase activity and induction of apoptosis might be a selective effect on cancer cells. Costunolide has been indicated to inhibit telomerase activity in human breast carcinoma cells.…”
mentioning
confidence: 99%
“…13) Most normal human cells have no detectable telomerase activity, but it is observed in most cancer cells 14,15) The inhibition of telomerase causes a progressive and critical reduction of telomeres, leading to a potent signal for the blockage of cell proliferation and the induction of apoptosis. 16) Targeting the inhibition of telomerase activity and induction of apoptosis might be a selective effect on cancer cells. Costunolide has been indicated to inhibit telomerase activity in human breast carcinoma cells.…”
mentioning
confidence: 99%
“…This enzyme is expressed in more than 85% of human tumors and compensates the loss of telomeres at each round of replication, thus contributing to cancer survival. 25,26 In another scenario, Pt(II)-terpy complexes were found to inhibit the growth of different morphological forms of Trypanosoma cruzi and Trypanosoma brucei, the parasitic protozoa causative agents of Chagas' disease and African trypanosomiasis (sleeping sickness), respectively. 27,28 Finally, Pt(II)-terpy derivatives with luminescence properties have been studied for bioimaging as DNA staining agents 29 and biotinylated Pt(II)-ferrocenylterpyridine complexes were also tested for targeted photoinduced cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, functional and mechanistic studies have suggested that TERT acts as a direct transcriptional regulator of oncogenic signaling pathways that not only modulate its own levels but also control the induction of target genes critical for cell survival and cancer progression [ 8 , 17 20 ]. What is more, telomerase is reported to be the target of many kinds of anticancer agents, and both telomerase inhibition and telomere dysfunction have been demonstrated as a consequence of platinum treatment, suggesting the potential influence of TERT on treatment efficacy of platinum-based chemotherapy [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%